2016
DOI: 10.5530/fra.2017.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical- and Cell-based Antioxidant Capacity of Methanolic Extracts of Three Commonly Edible Plants from Zingiberaceae Family

Abstract: Background: Edible plants belonging to the Zingiberaceae family display various antioxidative properties and widely used as folklore medicines. Three edible plants in Zingiberaceae family; namely Boesenbergia rotunda, Phaeomeria imperialis and Zingiber officinale were selected for secondary metabolites extraction using methanol. All crude extracts were investigated to evaluate their phenolics and flavonoids contents and further compare their antioxidant properties. Methods: Total phenolic content and total fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Rao et al (2010) reported that the ability of the extracts to reduce Fe 3+ could be attributed to the number of hydroxyl groups in the phenolic and flavonoid compounds. Chiang et al (2017) reported that FRAP and DPPH radical scavenging ability could be attributed to the flavonoids present in plant extract of Zingiberaceae family.…”
Section: Discussionmentioning
confidence: 99%
“…Rao et al (2010) reported that the ability of the extracts to reduce Fe 3+ could be attributed to the number of hydroxyl groups in the phenolic and flavonoid compounds. Chiang et al (2017) reported that FRAP and DPPH radical scavenging ability could be attributed to the flavonoids present in plant extract of Zingiberaceae family.…”
Section: Discussionmentioning
confidence: 99%
“…According to the traditional heritage, mentioned in a book published by AgroMedia (2007), fingerrot are often used to sprue, dry cough, skin diseases or diarrhea. The phytochemical content of the fingerroot rhizome has been used as antibacterial, anticancer, anti-inflammatory, and antioxidant (Zainin, et al, 2013;Udomthanadech, et al, 2015;Cheah, et al, 2011;Isa, et al, 2012;Chiang, et al , 2017).…”
Section: Fingerroot and The Utilization By The Societymentioning
confidence: 99%
“…The rhizomes of B. rotunda have been used as spices, flavoring agents, dyes and as traditional medicine. The uses or phytochemical properties of B. rotunda from several literature reviews are anti-allergic,[ 22 ] antibacterial,[ 23 24 ] anti- Helicobacter pylori ,[ 25 ] anti-leptospiral,[ 26 ] anticancer,[ 27 28 ] anti-inflammatory,[ 29 ] antioxidant,[ 30 ] antiulcer,[ 31 ] and anti-dengue viral,[ 32 33 ] and anti-herpes viral activities[ 34 ] and wound healing. [ 35 ] It also uses to treatment hepatic disease.…”
Section: Traditional Usesmentioning
confidence: 99%